Preoperative dexamethasone for pain relief after total knee arthroplasty: A randomised controlled trial. Issue 12 (December 2020) - Chan, Timmy Chi Wing; Cheung, Chi Wai; Wong, Stanley Sau Ching; Chung, Arthur Yu Fai; Irwin, Michael G.; Chan, Ping Keung; Fu, Henry; Yan, Chun Hoi; Chiu, Kwong Yuen
Abstract : BACKGROUND: Corticosteroids can reduce pain but the optimal dose and safety profiles are still uncertain. OBJECTIVE: This study aimed to evaluate two different doses of dexamethasone for pain management and their side effects after total knee arthroplasty. DESIGN: A prospective randomised, controlled trial. SETTING: A tertiary teaching hospital in Hong Kong. PATIENTS: One hundred and forty-six patients were randomly allocated to one of three study groups. INTERVENTIONS: Before operation, patients in group D8, D16 and P received dexamethasone 8 mg, dexamethasone 16 mg and placebo (0.9% saline), respectively. MAIN OUTCOME MEASURES: The primary outcome was postoperative pain score. Secondary outcomes were opioid consumption, physical parameters of the knees and side effects of dexamethasone. RESULTS: Compared with placebo, group D16 patients had significantly less pain during maximal active flexion on postoperative day 3 [−1.3 (95% CI, −2.2 to −0.31), P  = 0.005]. There was also a significant dose-dependent trend between pain scores and dexamethasone dose ( P  = 0.002). Compared with placebo, patients in group D16 consumed significantly less opioid [−6.4 mg (95% CI, −11.6 to −1.2), P  = 0.025] and had stronger quadriceps power on the first three postoperative days (all P  < 0.05). They also had significantly longer walking distance on postoperative day 1 [7.8 m ([95% CI, 0.85 to 14.7), P  = 0.023] with less assistance during walking on the first two postoperative days (all P  < 0.029) and significantly better quality-of-recovery scores on postoperative day 1 ( P  = 0.018). There were significant dose-dependent trends between all the above parameters and dexamethasone dose (all P  < 0.05). No significant differences were found in the incidence of chronic pain or knee function 3, 6 and 12 months postoperatively. CONCLUSION: Dexamethasone 16 mg given before total knee arthroplasty led to a reduction in postoperative pain, less opioid consumption, stronger quadriceps muscle power, better mobilisation and better overall quality-of-recovery after operation. No long-term improvement in reduction in pain and function of the knee was found. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT02767882. Abstract : Supplemental Digital Content is available in the text